Síntese de biodiesel por transesterificação do óleo da amêndoa da castanha do caju utilizando catálise heterogênea - Uchôa, Antonia Flávia Justino (2017)
Well-ordered KIT-6 mesoporous silica was synthesized through a co-condensation method and functionalized with sulfonic acid groups and also with zirconium. The synthesized catalysts were characterized by small-angle X-ray diffraction (SAXS), transmission electron microscopy (TEM), FT-IR spectroscopy, Thermogravimetric analysis, 13C solid-state NMR, 29Si solid-state NMR, wide-angle X-ray diffraction (XRD), elemental analysis and N2 adsorption-desorption measurements. Small angle X-ray diffraction spectroscopy confirmed formation of well-ordered mesoporous KIT-6 material. The BET analysis showed a high surface area and well-ordered support formed. The XRD analysis demonstrated the loaded Zr existed almost wholly as ZrO2 phases and after calcination converted mainly to the form of ZrO4 phase on KIT-6. The material KIT-6 functionalized with sulfonic acid groups was then used as acid heterogeneous catalyst for the transesterification of cashew nut oil with butanol to produce biodiesel. Reusability behavior of the catalyst was also demonstrated. As a result, KIT-6 propylsulfonic acid catalyst has shown a good catalytic activity. The catalyst is able to produce a yield to butyl ester over 70% as determined by 1H NMR spectroscopy in 6 h of reaction with a molar ratio (30:1), 140 °C and a 6 wt% of catalyst mass relative to starting oil mass in the reaction. KIT-6 propylsulfonic acid catalyst could be recycled and reused for at least three cycles without significant decrease in activity and stability. In addition, there was no by-product.